2022
DOI: 10.1111/flan.12618
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inserted adjunct questions on L2 reading with Chinese learners

Abstract: The present study examines the effect of adjunct questions on the reading comprehension of English‐speaking learners of Chinese as a second language (L2). In Experiment 1, fourth‐year (advanced) learners (n = 42) read two texts, either with or without adjunct questions, and completed a multiple‐choice cloze. In Experiments 2 and 3, second‐year (intermediate) learners (n = 40 and 34, respectively) read two texts, either with or without adjunct questions, and completed multiple‐choice cloze (Experiment 2) and wr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 66 publications
1
11
1
Order By: Relevance
“…The results showed that the readers' L2 proficiency and prior subject knowledge did not enhance the effects of embedded adjunct questions on reading comprehension [9]. A more recent study with intermediate and advanced learners of Chinese found that the adjunct questions only had positive effects on readers of intermediate levels with written recall as a comprehension assessment, but not on advanced L2 learners [10].…”
Section: Learners' Language Proficiencymentioning
confidence: 84%
See 4 more Smart Citations
“…The results showed that the readers' L2 proficiency and prior subject knowledge did not enhance the effects of embedded adjunct questions on reading comprehension [9]. A more recent study with intermediate and advanced learners of Chinese found that the adjunct questions only had positive effects on readers of intermediate levels with written recall as a comprehension assessment, but not on advanced L2 learners [10].…”
Section: Learners' Language Proficiencymentioning
confidence: 84%
“…Some have tried the analogy method to assist adult L2 comprehension with domain-specific text types [18,19]. When analogies failed to achieve the expected positive effect on L2 reading comprehension, other researchers began to hypothesize the influence of adjunct questions on the L2 reading comprehension because this method has been proven to be beneficial in L1 reading [3][4][5][6][7][8]10,14]. The limited number of studies conducted so far examined and analyzed variables such as learners' L2 language proficiency level, the embedded question types, methods used to deal with the inserted adjuncts, and the types of assessment tasks for reading comprehension and text types.…”
Section: Textual Enhancement In L2mentioning
confidence: 99%
See 3 more Smart Citations